Additive-Free Palladium-Catalysed Hydroamination of Piperylene with Morpholine - Neubert, Peter; Meier, Ines; Gaide, Tom; Behr, Arno (Synthesis, 2016)
In this contribution, the additive-free hydroamination of piperylene, an easily accessible 1,3-diene from naphtha steamcracking, with morpholine is described. This reaction provides an atom economic access to allylic C5 amines in a single step from commercially available and air-stable precursors and ligands. Detailed investigations revealed (DPPB)Pd(CCl3CO2)2 as the most active catalyst. After a 12-hour reaction period, a total yield of 79% allylic amines was obtained in the presence of 0.3 mol% catalyst. Furthermore, a noteworthy influence of the catalyst counter ion and the substrate concentration was discovered.
Keywords: homogeneous catalysis; hydroamination; dienes; amines; additive-free; piperylene; palladium